Ruminant farmers' knowledge, attitude and practices towards zoonotic diseases in Selangor, Malaysia - Sadiq, Mohammed Babatunde; Abdul Hamid, Norhamizah; Yusri, Ummu Khalisah; Ramanoon, Siti Zubaidah; Mansor, Rozaihan; Affandi, Syahirah Ahmad; Watanabe, Malaika; Kamaludeen, Juriah; Syed Hussain, Sharifah Salmah (Elsevier BV, 2021)
This study aimed to assess knowledge, attitude and practices about zoonotic diseases and associated factors among ruminant farmers in Selangor, Malaysia. A cross-sectional survey was conducted between January 2018 and December 2020. The survey was developed in English and Malay, validated, administered to ruminant farmers in Selangor. A total of 84 farmers completed the structured questionnaire. The data were analysed using descriptive statistics, principal component factor analysis and binary logistic regression models. Only 42 % (35/84) had heard of the term “zoonotic diseases” before this study but the majority of farmers (52/84; 61.9 %) were aware that certain diseases could be transmitted between humans and animals. A higher proportion was aware of rabies (20.8 %), followed by tuberculosis (17.8 %) and brucellosis (15.7 %), and most respondents identified the diseases as zoonotic. The majority of farmers stated (60 %) that zoonosis could be prevented and they preferred to learn more about such diseases through veterinary personnel. Higher proportions (>80 %) agreed to practices such as hand washing, proper cooking of meat, and keeping animal health records. However, the need to pasteurise milk before drinking and selling were the least items that farmers agreed to, which was reflected in their practices. Sixty-four per cent of the farmers had stray animals on their farm with dogs (45.5 %) being predominant. Overall, 34.5 % (29/84), 51.1 % (43/84), and 60.7 % (51/84) were considered to have satisfactory knowledge, attitude and practices regarding zoonotic diseases, respectively. Farmers with higher education (odds ratio; OR = 16.6; 95 % CI 3.7−71.4) and rearing exotic breeds of animals (OR = 6.0; 95 % CI 1.3–27.7) were more likely to have satisfactory knowledge about zoonoses, but less likely for those with small herd size (51−100 animals) (OR = 0.19; 95 % CI 0.04−0.95). The odds of having satisfactory attitude towards preventive measures against zoonoses were higher in farmers with higher education (OR = 3.2; 95 % CI 1.1−8.9). Farms with herd health programs were more likely to engage in satisfactory practices towards zoonoses (OR = 3.2; 95 % CI 1.2−10.0) relative to farms lacking programs. These areas might need to be considered by public health authorities to improve the current knowledge and attitude of ruminant farmers about zoonotic diseases in the Malaysian context.